Editorial - Hiemstra, Djoerd; Altingovde, Ismail; Atnafu, Solomon; Godoy, Daniela; He, Ben; Kato, Makoto; Liang, Shangsong; Liu, Haiming; Murdock, Vanessa; Paramita, Monica; Poblete, Barbara; Rahimi, Negin; et al. (Information Retrieval Research, 2025)
This editorial celebrates the first issue of the Information Retrieval Research Journal, IRRJ.